2021
DOI: 10.1016/j.ypmed.2021.106566
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of muscle-strengthening exercise in public health surveillance for adults: A systematic review

Abstract: There is strong scientific evidence that muscle-strengthening exercise (i.e. use of weight machines, push-ups, situps) is independently associated with a reduced risk of multiple chronic diseases (e.g. diabetes, hypertension, cardiovascular disease). However, prevalence rates for meeting the muscle-strengthening exercise guideline (≥2 times/week) are significantly lower (~20%) than those reported to meet the aerobic physical activity guideline (e.g. walking, jogging, cycling) (~50%). It is therefore important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 161 publications
0
30
0
3
Order By: Relevance
“…Percentage agreement for four types of MSE and the types combined was excellent (range 75.9%-96.3%), except for 'back' when doing Overall, among our active, young, and well-educated sample, the MSEQ showed substantial test-retest reliability and adequate validity when using a 7-day MSE log as the standard. While these findings need to be replicated in studies with a more representative sample, this Few studies have reported on the reliability and validity of existing MSE survey instruments, but 19 comparing our findings to similar studies is limited. For weekly MSE frequency, the MSEQ shows similar reliability and stronger validity compared with the MSE item from the BRFSS using a physical activity log.…”
Section: Test-retest Reliabilitymentioning
confidence: 65%
See 4 more Smart Citations
“…Percentage agreement for four types of MSE and the types combined was excellent (range 75.9%-96.3%), except for 'back' when doing Overall, among our active, young, and well-educated sample, the MSEQ showed substantial test-retest reliability and adequate validity when using a 7-day MSE log as the standard. While these findings need to be replicated in studies with a more representative sample, this Few studies have reported on the reliability and validity of existing MSE survey instruments, but 19 comparing our findings to similar studies is limited. For weekly MSE frequency, the MSEQ shows similar reliability and stronger validity compared with the MSE item from the BRFSS using a physical activity log.…”
Section: Test-retest Reliabilitymentioning
confidence: 65%
“… 28 Given that at the population level, ~60% of adults do no MSE, 29 an understanding of what constitutes MSE may be limited among the general population. 19 Therefore, to assist respondents, we provided the following statement at the beginning of the survey:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations